Guanidinium tetrabromidomercurate(II) - Terao, Hiromitsu (International Union of Crystallography, 2009)
The Hg atoms in the crystal structure of the title compound, (CH(6)N(3))(2)[HgBr(4)], are tetrahedrally coordinated by four Br atoms and the resulting [HgBr(4)](2−) tetrahedral ions are linked to the [C(NH(2))(3)](+) ions by bromine–hydrogen bonds, forming a three-dimensional network. In the structure, the anions are located on special positions. The two different Hg⋯Br distances of 2.664 (1) and 2.559 (1) Å observed in the tetrabromidomercurate unit are due to the connection of Br atoms to different number of H atoms.